2015
DOI: 10.2196/jmir.4304
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reaction Identification and Extraction in Social Media: A Scoping Review

Abstract: BackgroundThe underreporting of adverse drug reactions (ADRs) through traditional reporting channels is a limitation in the efficiency of the current pharmacovigilance system. Patients’ experiences with drugs that they report on social media represent a new source of data that may have some value in postmarketing safety surveillance.ObjectiveA scoping review was undertaken to explore the breadth of evidence about the use of social media as a new source of knowledge for pharmacovigilance.MethodsDaubt et al’s re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
97
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 52 publications
3
97
0
Order By: Relevance
“…A variety of studies have sought to determine the value of social media data in the context of traditional pharmacovigilance (PV) methodologies [1][2][3][4]. These studies have also tried to advance the analysis of social media data to Electronic supplementary material The online version of this article (doi:10.1007/s40290-017-0186-6) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of studies have sought to determine the value of social media data in the context of traditional pharmacovigilance (PV) methodologies [1][2][3][4]. These studies have also tried to advance the analysis of social media data to Electronic supplementary material The online version of this article (doi:10.1007/s40290-017-0186-6) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have also tried to advance the analysis of social media data to Electronic supplementary material The online version of this article (doi:10.1007/s40290-017-0186-6) contains supplementary material, which is available to authorized users. improve its use for monitoring the safety of drugs and devices [1][2][3][4]. The use of social media data for tracking 'posts with resemblance to adverse events' (proto-AEs) is an evolving science within PV [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of social media allows large groups of people to create and share information, opinions, and experiences about health conditions and medications through online communications [5]. Social media provide pharmacovigilance experts with a relevant source of information [6]. The example of benfluorex [7] illustrated how social media could be valuable sources for experts.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Even though drugs are monitored in clinical trials for safety prior to approval and marketing, not all ADRs are reported due to the short duration and number of patients registered in clinical trials. Therefore, post marketing surveillance of ADRs is of utmost importance [1,2]. Reporting of ADRs is commonly done by medical practitioners.…”
Section: Introductionmentioning
confidence: 99%